AN INVESTIGATION INTO THE PRONUNCIATION OF ENGLISH STRESS PERFORMED BY VIETNAMESE STUDENTS OF ENGLISH AT GIALAI JUNIOR COLLEGE OF EDUCATION - Ph D. Ngũ Thiện Hùng (Trường Đại học Ngoại ngữ, 2025)
To investigate how English stress are perceived and performed by the students at Gialai Junior College of Education; To identify the errors they make and the causes leading to their making mistakes in the process of performing stress; To provide them with practical knowledge to overcome their problems in performing stress.